RELATIONSHIP BETWEEN HEALTH BEHAVIORS AND QUALITY OF LIFE ON THE ONE HAND AND SATISFACTION WITH HEALTH CONDITION ON THE OTHER HAND IN PATIENTS WITH PSORIASIS - Mariusz Jaworski (Our Dermatology Online, 2013)
Introduction: Scientific research suggest that the more severe psoriasis symptoms are the poorer quality of life. Reviews show that appropriate health practices can reduce severity of symptoms of some diseases on the one hand and influence subjective assessment of quality of life on the other hand. The authors tried to assess the frequency of health behaviors in patients with psoriasis compared to the control group, as well as to analyze the relationship between health behavior and the quality of life. Materials and Methods: The study was conducted on 61 patients with psoriasis and 60 respondents as a control group. Two tools were used in the study: Behavioral Health Inventory and author's questionnaire with questions concerning quality of life, satisfaction with health condition, number of medicines used and severity of psoriasis. Statistical analyzes were performed using Statistica SPPS 18. Results: Patients with psoriasis assessed as worse their quality of life compared to the control group. In case of intensity of healthy eating habits the similar differences were revealed. Inverse relation was observed in case of prevention behaviors. There were no differences between the groups in terms of positive mental attitude and health practices. Quality of life in patients with psoriasis correlated with a positive mental attitude. Conclusions: Our results suggest the need for comprehensive education in three areas: medical, nutritional and psychosocial. .